THE MANAGEMENT OF CORPORATE CULTURE IN RUSSIA BASED ON THE DYNAMIC CONCEPT - M. Ermoshin (Вестник университета)
The arguments substantiating the need for management of corporate culture in Russia are presented. The advantages of the spiral model of development of the corporate culture are identified. The basic stages of development of corporate culture are described. The general state of the corporate culture of russian enterprises is assessed. The general recommendations for managing of corporate culture are given.